Robust observer design for Sugeno systems with incremental quadratic nonlinearity in the consequent - Moodi, Hoda; Farrokhi, Mohammad (Zielona Góra: Uniwersytet Zielonogórski)
This paper is concerned with observer design for nonlinear systems that are modeled by T-S fuzzy systems containing parametric and nonparametric uncertainties. Unlike most Sugeno models, the proposed method contains nonlinear functions in the consequent part of the fuzzy IF-THEN rules. This will allow modeling a wider class of systems with smaller modelling errors.
Keywords: nonlinear Sugeno model; incremental quadratic constraint; robust observer